İslam hukukunda zina suçu ve cezası - Boynukalın, Mehmet (My University, 1995)
Yenilenme/ Tecdid İslam düşüncesine yabancı bir kavram değildir. Ancak İslami literatürde yenilenme terimi Kuran ve Sünnet'e dönmeyi, diğer bir ifadeyle İslamı, Hz. Peygamber'in tebliğ ve uygulamalarına uygun bir biçimde anlamayı ve bu dinin hükümlerini hayata geçirmeyi ifade etmektedir. Bu kavramın tam karşısında dinin özüne ve açık hükümlerine aykırı yenilikleri içeren bidat kavramı yer almaktadır. Bu bakımdan Kuran ve Sünnet'in anlaşılmasında izlenecek yöntemleri ele alan fıkıh usulünde yenilenmenin sınırlarını bu çerçeve içinde kalarak belirlemek gerekmektedir. Bilindiği üzere tarih boyunca İslam hukuku Müslümanların bireysel ve toplumsal hayatını düzenleyen ve yönlendiren en önemli etkenlerden biri olmuştur. Dolayısıyla batı ile karşı karşıya gelindiğinde belki de en belirgin çatışma hukuk alanında yaşanmıştır. Pratikte İslam dünyasının bir çok bölgesinde aşamalı bir biçimde yürürlükten kaldırılan İslam hukuku alanında, bu yöndeki uygulamalara paralel bir biçimde gelişen teorik çalışmalar da son yüz elli yılın her döneminde var olmuştur.

olarak söylemek gerekirse Kuran ve Sünnet'te kesin olarak sabit olmuş ve Hz. Peygamber'in uygulamasına tanık olan sahabe döneminden itibaren İslam alimlerinin görüş birliğiyle açıkladıkları şer'i hükümlerin - geçici zaruri durumlar müstesna - değiştirilmesine yol açan herhangi bir metodolojinin kabulü mümkün değildir. Bu esasların dışında kalan hükümler ise zaten ictihada açık oldukları için bu alana yönelik metodolojik ilkelerin değişmesi ve bu anlamda fıkıh usulünde yenilenme geçmişte olduğu gibi günümüzde de mümkündür ve buna önemli ölçüde ihtiyaç hissedilmektedir. Bu çerçevede tezde bazı çağdaş fıkıhçı ve düşünürlerin Kuran ve Sünnet'in yorumu, Sünnet'in sübutu, icma, istislah ve örf gibi konularla ilgili görüşleri incelenmiştir. The revival/ tajdeed in the thought of Islamic terminology is not new. The statement of revival in Islamic literature, however, means to return to the path of Qur'an and Sunnah (traditions of the prophet of Islam) or with another way of saying, is to understand Islam in a suitable manner and follow it in our daily life according to the religious laws as given in the Qur'an and the hadiths/ sayings' of Prophet Mohammed (pbh) and his traditions. A contrary statement to the above mentioned one, known as bid'ah, which means new things; those are normally considered to be against the principles and the thyme of the religion. Therefore, without any change about the way of principles in understanding the Qur'an and Sunnah, it is necessary define the boundary of revival within the framework of feqh has to be explained. As known throughout the history, the Islamic laws (Shariah of Islam), which guides and arrange the life of individual believers and the whole Islamic society were an important factor. Therefore, it is seen that the biggest outstanding clash was occurred in the field of jurisprudence when faced with the west. As seen in practice that the Islamic laws have been gradually outlawed in most of the Islamic countries, beside that, however, a developing theoretical work have been done in the same field within the last half of the century. In summary, it is impossible to accept a methodology which allows to change the fundamental Islamic judgements as expressed according to the Qur'an & Sunnah and the common view of scholars (ajmaa' ummah) from the time of sahabah ( the companions of Prophet Mohammed pbh) who witnessed the life style of the prophet of Islam. These are obviously accepted with the exception of certain temporary and difficult conditions. However, the judgements staying out of the above conditions are subjected to discussions. Therefore, in this context, the revival in feqh (Islamic jurisprudence) is possible in nowadays studies as used to be in the past. It is believed that the existing Islamic society has been feeling its necessity at the highest level. Within this framework, the interpretation of Qur'an & sunnah by some contemporary faqehs/ scholars and their views about subutu sunnah, ajmaa', istislah and customs related subjects are discussed in the thesis.
Keywords: Din; Fıkıh ve fıkıh ilmi; HUKUK-İSLAM HUKUKU-ZİNA SUÇU; İslam Dini